A Substitute of Ultrasound Acoustic Stand-Off Pad Made From Locally Available Material: An innovation to Survive in Resource Limited Conditions - Moudgil, Sandeep; Singh, Lokesh; Raina, Sunil (Archives of Clinical and Biomedical Research, 2021)
Introduction: The use of stand-off acoustic pads for ultrasonographic evaluation of the superficial structures is well established. These are costly and not available readily at peripheral and remote community level institutes like ours. This instigated to make a simple and cheaper substitute to these stand-off pads. A cost effective alternative for these commercial acoustic stand-off pads made by using locally available condom and ultrasound jelly is presented here. Material and Methods: A latex condom, commonly available in hospital supplies, was filled with ultrasound coupling jelly. All the air was removed and a knot was secured at the end. The coupling jelly was applied between the skin condom and condom transducer interface while scanning. Superficial lesion of different body regions, breast and superficial foreign bodies were evaluated using the condom stand off pads. Observations: Scanning the area of interest using condom stand-off pad showed the overlying skin details, depth of lesion from the skin, internal architecture of the lesion and surrounding tissue in more detail than scanning without pad. The image quality of breast tissue or lesions located just below the nipple in sub retro-areolar region was better than these areas of interest scanning without pad. It also aided in evaluating the depth of superficial foreign body from the skin surface which helped in their surgical or image guided retrieval. Conclusion: The material used in making these condom stand-off pads is easily available and very cheap. The condom stand-off described here will help the radiologists working in remote or rural areas by providing them an easy to make and cheaper substitute in a resource limited setting. The quality of image and ease to handle is not as that of commercially available stand-off pads nevertheless condom stand-off pads